Sexual Harassment Experienced by the Women in Novel “Women Talking” By Miriam Toews - Ida Epi Hariati Dongoran; Robby Satria (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
This research was conducted to figure out the sexual harassment, causes and effect experienced by the women in the novel women talking by Miriam Toews.This study used feminist approach with theory by Rosemarie Tong. Sexual harassment was behavior that approaches related to unwanted sex, including the demand for sex, and other behaviors being verbally or physically refer to sex more. This study aimed to find out the cause and effect of the sexual harassment experienced by the women in the Molotschna colony as seen in women talking novel. This study used descriptive qualitative to analyze the social problems that found in the novel. The result of the study,there were two causes and effects of the sexual harassment in the novel of women talking. The first cause of the sexual harassment in the novel of women talking was the gender gap. Gender gap made people considered that the position of women and men was very different. Men were superior and strong while women were the opposite.The second cause was the male domination. Patriarchy construction placed women as a weak creature that can be control by the men.The effects of sexual harassment that received by the women in the novel physically and psychologically.They were injured physically and their health was disturbed psychologically